An Exploration of Chinese Percussion Instruments from the Perspective of "Category, Art, and Function" (Journal of Global Arts Studies, 2024)
Background: As one of the oldest and most significant types of musical instruments in China, percussion instruments have received substantial attention and emphasis from the Chinese government in terms of cultural preservation and transmission. Objective: This study aims to explore and analyze the classification characteristics, artistic forms, cultural connotations, and societal value of Chinese percussion instruments. Methods: By employing literature review and case analysis, the classification, performance forms, and intrinsic and functional values of Chinese percussion instruments were systematically examined. Results: The findings reveal that Chinese percussion instruments are primarily categorized into four groups: "drums, bronze percussion, clappers, and others." Over their extensive development, these instruments have evolved into diverse artistic expressions, ranging from collective to individual performances and from raw simplicity to refined sophistication. Moreover, they have played pivotal roles across various contexts, including political, religious, and folk traditions. Conclusion: Percussion instruments are not only a treasured asset of Chinese musical art but also a vital carrier of China's historical and cultural legacy and spiritual civilization. Across different eras and humanistic contexts, they have fulfilled multifaceted functions in politics, military, culture, art, and social practices, making an indelible contribution to the development and transmission of Chinese civilization.
Keywords: Chinese percussion instruments; instrument classification; artistic forms; cultural connotations